2018
DOI: 10.1111/jfb.13651
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of masculinization by continuous illumination in a temperature sex determination teleost (Atherinopsidae) model: is oxidative stress involved?

Abstract: The present study evaluates the influence of continuous light on phenotypic sex ratios in Chirostoma estor, a temperature sex determination animal model. Relative gene expression levels of 5 day old larvae were performed on two early gonad differentiation genes (sox9 and foxl2), two stress axis activation genes (gcr1 and crf) and four reactive oxygen species (ROS) antagonist effector genes (sod2, ucp2, gsr and cat). Two light treatments were applied from fertilization; control (12L:12D) simulated natural photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Interestingly, this study also uncovered compelling evidence of the influence of daylength during early development on sex determination in cobaltcap silverside, with short and long daylengths inducing masculinization and feminization, respectively (Figure ). This places this species together with the grunion (Brown et al., 2014) and the pike silverside (Corona‐Herrera et al., 2018), other atheriniforms in which sex determination is affected by photoperiod. Although this finding still needs to be scrutinized in carefully conducted laboratory experiments, including the evaluation of synergistic and antagonistic effects with temperature, in hindsight, it may help explain the seemingly paradoxical formation of sex‐reversed males at the relatively low temperatures early and late in the breeding season, the inconsistency between results for wild and reared XY models, as well as the occurrence of some sex‐reversed females at high temperatures in the laboratory experiments (which used a long 14 hr photoperiod).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, this study also uncovered compelling evidence of the influence of daylength during early development on sex determination in cobaltcap silverside, with short and long daylengths inducing masculinization and feminization, respectively (Figure ). This places this species together with the grunion (Brown et al., 2014) and the pike silverside (Corona‐Herrera et al., 2018), other atheriniforms in which sex determination is affected by photoperiod. Although this finding still needs to be scrutinized in carefully conducted laboratory experiments, including the evaluation of synergistic and antagonistic effects with temperature, in hindsight, it may help explain the seemingly paradoxical formation of sex‐reversed males at the relatively low temperatures early and late in the breeding season, the inconsistency between results for wild and reared XY models, as well as the occurrence of some sex‐reversed females at high temperatures in the laboratory experiments (which used a long 14 hr photoperiod).…”
Section: Discussionmentioning
confidence: 94%
“…and the pike silverside(Corona-Herrera et al, 2018), other atheriniforms in which sex determination is affected by photoperiod. Although this finding still needs to be scrutinized in carefully conducted laboratory experiments, including the evaluation of synergistic and antagonistic effects with temperature, in hindsight, it may help explain the seemingly paradoxical formation of sex-reversed males at the relatively low temperatures early and late in the breeding season, the inconsistency between results for wild and reared XY models, as well as the occurrence of some sex-reversed females at high temperatures in the laboratory experiments (which used a long 14 hr photoperiod).…”
mentioning
confidence: 99%
“…One of these genes, UCP2 , was upregulated at high male producing temperatures in A. mississippiensis (82). UCP2, and others genes involved in oxidative stress responses, were also implicated in UV induced masculinisation in larvae of a thermosensitive fish species ( Chirostoma estor ) (118). Notably, we found that UCP2 was upregulated between stages 6 to 12 in ZZf P. vitticeps embryos, suggesting a sustained response to thermal stress in the mitochondria (Additional file S3).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we propose a general model in which sex determination is mediated by cellular calcium (Ca 2+ ) and redox (reactive oxygen species; ROS) status, which are subject to environmental influence. Elements of this hypothesis have been discussed in six recent papers that explicitly posited the involvement of either ROS production or Ca 2+ flux in directing the outcomes of ESD (Yatsu et al ., , ; Czerwinski et al ., ; Corona‐Herrera et al ., ; Lin et al ., ; Hayasaka et al ., ). We suggest that these two interrelated signalling systems (Richter & Kass, ) work together to initiate sex determination.…”
Section: Introductionmentioning
confidence: 99%